ANALYSIS OF GOVERNMENT PERFOMANCE (Case Study of Local Goverment Rejang Lebong) - Meriana (Jurnal Ilmiah Raflesia Akuntansi, 2019)
- This study aims to determine the financial performance of Rejang Lebong Regency Government. The analysis used in this research is Financial Ratio with Qualitative, using 5 (five) Ratio that is, Degree of Fiscal Decentralization Degrees Independence Ratio, Efficiency Ratio, Effectiveness Ratio and Ratio of Harmony. Uses from the Rejang Rejang Revenue Budget Report from 2014 to 2016. The results of this study can be concluded that the Financial Performance of Rejang Lebong Regency is the comparison of financial performance from 2014 to 2016 which is still less satisfactory, since the original income of Rejang Lebong Regency is still relatively low compared to the Self Transfer Local Income. In terms of revenue the original district rejang lebong still very less because it is still dependent on the Transfer from the center. From effectiveness is also still less effective, from efefiensi still less efficient because the average is still equal to 97,34%. In terms of harmony also operational spending is still greater than the capital spending Rejang Lebong Regency.